PERANCANGAN INTERFACE MOBILE START UP â€œSERVICE INâ€ MENGGUNAKAN METODE DESIGN THINKING DAN ANALISIS GSTALT - Lubis, Hendarman; Harun, Rofiq; Rahma, Dea Wemona; Satrinia, Dwina (TRANSFORMASI, 2025)
The development of digital technology has encouraged the emergence of various mobile application-based services to facilitate daily activities. The Service In application is present as a digital start-up solution that provides online technician booking services via mobile devices. The development method used in this study is the Design Thinking Method which consists of the stages of Empathize, Define, Ideate, Prototype and Test. The GSTALT principle consisting of; Proximity, Similarity, Common-region, Focal point, Continuity, Closure and Figure/ground is used in designing the user interface of the "Service In" mobile application. In this study, the UI design testing process uses the Usability Heuristic indicator to be able to observe user activity. The testing results obtained a value of 79% which indicates that the Service.in start-up falls into the user friendly criteria.Keywords: Start Up, Design Thinking, GSTALT, Service In, Usability Heuristic